Giant Magnetoimpedance in Electrodeposited Cobalt on Silver Wires - JANTARATANA, Pongsakorn; SIRISATHITKUL, Chitnarong (Walailak Journal of Science and Technology (WJST), 2011)
Cobalt of thickness from 1 to 25 mm was coated onto 120 mm-diameter silver wires by electrodeposition. Giant magneto-impedance (GMI) of electrodeposited cobalt on silver wires was measured with ac current from 1 kHz to 1 MHz. Their impedance decreased with a longitudinal magnetic field and saturated under 1.5 kOe. With increasing cobalt thickness, the critical frequency decreased but the GMI ratio increased. A maximum GMI ratio of over 200 % and sensitivity of about 0.5 %/Oe were observed in a 25 mm-thick sample at the frequency of about 500 kHz. The results can be explained by the dependence of the circumferential permeability on the magnetic field and frequency of ac current.